The Application of Cows Rumen for Electricity Generation Through The Implementation of A Ceramic-Based Microbial Fuel Cell System - Mulyono, Tri; Hutamia, Diah Meirendi; Rofi’i, Imam; Misto, M.; Nugroho, Agung Tjahjo; Hariadi, Yuda Cahyoargo (Jurnal ILMU DASAR, 2024)
The growth in population is not adequately matched by the corresponding increase in energy demand. The imperative for prioritizing the exploration of alternative energy sources that possess attributes of safety, affordability, and ample access to raw materials cannot be overstated. An energy source with significant potential is a microbial fuel cell (MFC)-based energy source. This study aims to investigate the utilization of cow rumen as a substrate and source of nutrition in the bioenergy system of microbial fuel cells (MFCs). The present study aims to investigate the impact of substrate concentration and bacterial incubation duration derived from bovine rumen bacteria on the attainment of optimal power density. The research employed a Dual Chamber Microbial Fuel Cell (MFC) device using a Proton Exchange Membrane (PEM) constructed from ceramic materials. Daily observations were conducted over a period of 30 days. The performance of MFC was assessed utilizing the polarization technique. The findings indicated that altering the proportion of bovine rumen bacterial substrates and the duration of bacterial incubation had an impact on the power density seen in the Microbial Fuel Cell (MFC) system. The optimal conditions were attained when the substrate concentration reached 3640 ppm and after 7 days, resulting in a maximum power density of 864 mW/m2.